Business Intelligence for the Programs of the Secretaries of Health, Education and Planning in a Territorial Entity - Varona-Taborda, Maria-Alejandra; Mosquera-Ramírez, Jorge-Cesar; Medina-Moreno, César-Augusto; Lemus-Muñoz, Diego-Fernando; Muñoz-Hernandez, Carlos-Julián; Arias-Iragorri, Christian-Gustavo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Territorial entities in Colombia are bound by the law to register and report to different instances the control information of the government programs they administer. However, so much information is distributed on various state and owned platforms that the result is processed and generated in different formats. This situation makes the comprehensive management of territorial data difficult, since, although the information exists, it is isolated, and its analysis is carried out independently by each party responsible for the process. The objective of this research is the Implementation of a business intelligence model that allows integration and analysis of data from the programs of the Health, Education, and Planning ministries for a Territorial Entity. Ralph Kimball's methodology was used, implementing a star topology model in the Datamart using MySQL as a database manager, an ETL system was built with the Pentaho tool which allows the extraction, transformation, and loading of the data in the Datamart. The cubes, reports and Dashboard are obtained with the management of tools such as Pentaho and Power BI, thus it is possible to make a correct interpretation of the resulting information. After applying Business Intelligence, it is possible to generate an adequate analysis of the information, allowing decision-making and application of new strategies to solve specific problems using control panels, visualization of indicators and generation of reports.